2017
DOI: 10.5194/hess-21-1421-2017
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of stemflow and its bio-/abiotic influential factors between two xerophytic shrub species

Abstract: Abstract. Stemflow transports nutrient-enriched precipitation to the rhizosphere and functions as an efficient terrestrial flux in water-stressed ecosystems. However, its ecological significance has generally been underestimated because it is relatively limited in amount, and the biotic mechanisms that affect it have not been thoroughly studied at the leaf scale. This study was conducted during the 2014 and 2015 rainy seasons at the northern Loess Plateau of China. We measured the branch stemflow volume (SF b … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 89 publications
3
21
0
Order By: Relevance
“…High Cv values indicate strong heterogeneities while values below 0.2 will be considered as acceptable, according to the standards of ASAE (1996) for irrigation uniformity. This threshold of 0.2 is also consistent with the reference values reported in Van der Gulik et al (2014).…”
Section: Sensitivity Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…High Cv values indicate strong heterogeneities while values below 0.2 will be considered as acceptable, according to the standards of ASAE (1996) for irrigation uniformity. This threshold of 0.2 is also consistent with the reference values reported in Van der Gulik et al (2014).…”
Section: Sensitivity Analysissupporting
confidence: 92%
“…For example, Diermanse (1999) showed that a correct simulation of runoff could often be achieved on the watershed scale from spatially averaged rainfall values, although clearly better results may be expected when explicitly accounting for the subscale spatial patterns of rain distribution (Faurès et al, 1995;Tang et al, 2007;Emmanuel et al, 2015). On the plot scale, rain interception and redistribution by the crops (Levia and Germer, 2015;Yuan et al, 2017) is already known to cause strong spatial heterogeneities (through stemflow, throughfall or improved water storage capabilities), thus raising multiple questions on soil microbiology, non-point source pollution and irrigation piloting (Lamm and Manges, 2000;Martello et al, 2015). The presence of solar panels will provide similar, additional issues close to those experienced in agroforestry when the vegetative cover is of various heights and nature, with a direct impact on the spatiotemporal patterns of rain redistribution (Jackson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Due to variation in plant morphology, the initiation and rate of production for stemflow may differ significantly among tree species [41][42][43][44]. In addition, there are notable differences in the absorption ability and material composition of the different plant organs and epiphytic organisms [27].…”
Section: Discussionmentioning
confidence: 99%
“…Stemflow is formed in the forest canopy, and recent work has strived to unveil how canopy architecture can regulate the formation of stemflow before being funnelled belowground (e.g. Levia et al, 2010Bialkowski and Buttle, 2015;Yuan et al, 2017;del Campo et al, 2018). However, tree architecture is complex (e.g.…”
Section: Introductionmentioning
confidence: 99%